E-commerce initiatives in the Malaysian shipping industry - Chooi, Leng Ang; Mat Tahar, Razman; Murat, Rusdi (2002)
Communication technology has always been important to a company.As this technology developed, it is increasingly being used as a strategic tool to re-engineer a business process and to gain competitive advantage.A majority of businesses and consumers have embraced electronic commerce (E-commerce) or “information exchange through an electronic means” to various extent.The electronic communications include E-mail, the internet, electronic fund transfer, electronic bulletin boards, file transfer protocols, barcodes for goods labeling and delivery, interactive voice response and electronic data interchange (EDI).EDI is about doing business and carrying out transactions with trading partners electronically.It is a paperless trading method and therefore an important foundation block for the implementation of Ebusiness. To harness the capability of EDI, Malaysian ports such as Port Klang was facilitated with the national EDI, Dagang*Net under the government’s trade facilitation program. The government hopes that EDI applications will bring about greater efficiency and productivity and also be able to respond to the needs and changing requirements of the trade if a port is to become a major port of call for shipping lines the world over. The advancement in information and communication technology (ICT) coupled with the intensification of ICT applications by all sectors prompted by the Multimedia Super Corridor (MSC) initiatives has propelled Malaysia into another level of technology exploitation – E-commerce.An understanding of their current status is essential for the success of any E-commerce initiatives in Malaysia.Thus this study seeks to provide such an empirical base.This study found that in the Malaysian shipping industry, EDI was primarily used in transactions with the Customs Department for duty payments and import/export declaration.The results indicated that EDI usage at Port Klang might be high in terms of volume. However, its use was still very low and limited in terms of diversity, breadth and depth. There was hardly any transaction between other business partners except the Customs Department.Although EDI has been introduced to the shipping community in the Port Klang area more than a decade ago, the port community has yet to fully realize the benefits that have been profusely talked about in literature and media.Generally, the three most cited benefits of EDI applications are the increase in efficiency, increase in data accuracy and increase in business image.This study also revealed that hidden computing costs, connectivity problems as well as network reliability and security were the major problems faced by these companies.